2012
DOI: 10.1097/rti.0b013e3182631c5c
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Computed Tomography Angiography in Patients With Chronic Chest Pain

Abstract: The diagnostic evaluation of patients without known coronary artery disease presenting with chronic stable chest pain or angina equivalent is complex. Imaging often plays a role in diagnosis and risk stratification, and a variety of techniques are available, each with inherent and situation-specific advantages and disadvantages. Coronary computed tomography angiography (CTA) has been proposed as a fast, noninvasive, reliable test to rule out disease in this population, with potential improvements in costs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Multiple studies have shown that CCTA is costeffective in patients with <50% pretest probability for ACS and also more cost-effective when used alone than when combined with SPECT MPI. 110 ROMICAT-II showed no significant difference in the cumulative mean cost of care for patients who underwent CCTA as opposed to an alternative noninvasive imaging modality. 74 Although patients with negative CCTA examinations had shorter hospital stays on their initial visit, they underwent more downstream testing and ultimately received more radiation exposure.…”
Section: Cost-effectivenessmentioning
confidence: 86%
“…Multiple studies have shown that CCTA is costeffective in patients with <50% pretest probability for ACS and also more cost-effective when used alone than when combined with SPECT MPI. 110 ROMICAT-II showed no significant difference in the cumulative mean cost of care for patients who underwent CCTA as opposed to an alternative noninvasive imaging modality. 74 Although patients with negative CCTA examinations had shorter hospital stays on their initial visit, they underwent more downstream testing and ultimately received more radiation exposure.…”
Section: Cost-effectivenessmentioning
confidence: 86%
“…Imaging often plays a role in diagnosis and risk stratification, and a variety of techniques are available, each with inherent and situation-specific advantages and disadvantages. Coronary CT angiography has been proposed as a fast, non-invasive, reliable test to rule out disease in this population, with potential improvements in costs and outcomes compared with alternative strategies [16]. The relatively rapid rise in coronary CT angiography utilization, however, has led to strong calls from doctors and health care policy organizations alike to provide high-level evidence supporting its use.…”
Section: Coronary Artery Disease (Cad)mentioning
confidence: 99%
“…They uniformly show that CCTA is able to achieve very high sensitivity and negative predictive value (both >95 %) and that its specificity and positive predictive value is moderate to high. Theoretically, on the basis of Bays’ theorem, these characteristics result in most useful application in low to intermediate prevalence populations, which are primarily encountered in the acute and stable chest pain setting [15, 16]. Among these populations, the high sensitivity and negative predictive value lead to substantial downward revision of probability; this enables safe rule-out of the disease of concern.…”
Section: Efficacy Of Ccta For Significant Coronary Stenosismentioning
confidence: 99%